BUKHARA IN 1920 (FOR THE 100TH ANNIVERSARY) - Gafurov Abdurauf (International Engineering Journal For Research & Development, 2020)
The article deals with illegal actions of Turkestan front headed by M. Frunze, who made an armed invasion into Bukhara emirate as a result of which Sacred Bukhara turned into ruin, the struggle between supporters and opponents of new social and economic relations intensified.